Isomery of SU3 states in the strictly restricted dynamics model - Katkevicius, O.; Krasta, T.; Ruza, J.; Tambergs, J.; Alcaras, JAC (Iop Publishing Ltd, 1999)
Employing the general principles of classification of SU3 states, we have found 285 quantum number isomers (QNI), i.e. nuclei for which there are two possible SU3 quantum number sets, characterized by the maximal eigenvalue of the SU3 group Casimir operator, at the minimal value N-0(min) for the quantum number N-0 of the group U3(A-1) symmetric representation, allowed by the Pauli principle. 41 of these QNI can be attributed to the nun-excited, ground SU3 configurations of realistic nuclei. Two examples of QNI: Si-28 and Zn-60, have been studied in detail in the framework of the strictly restricted dynamics model (SRDM).